Clustering Analysis of Employment Sectors According To OECD Countries Using The K-Average Method - İşleyen, Şakir (International Journal of Contemporary Economics and Administrative Sciences, 2021)
In addition to being one of the important parameters showing the welfare level of the countries, employment shows the economic development of the countries in which sector is concentrated. The existence of industry-based employment in developed or developing countries supports this situation. In addition, the resources of countries direct the employment policy of that country. It is stated in the literature that there is generally employment in this field in countries with high agricultural resources. In this study, the employment data of 36 OECD countries between 1991 and 2019 were analyzed using the Cluster analysis K-Average Method, which was obtained from the official web site of the World Bank. According to the employment data in Agriculture, Industry and Service sectors, it was analyzed in which cluster OECD countries are located and whether the variables show a meaningful clustering.